Kajian Minat Mahasiswa Prodi Pendidikan Bahasa Mandarin UKI terhadap Kelas Menyimak dan Berbicara Bahasa Mandarin - Belandina, Febe (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2023)
Learning Mandarin is considered quite difficult for everyone, especially Indonesian students. The main reason is because there is a huge difference between Indonesian as a mother tongue and Mandarin. Learning Mandarin means learning that includes four aspects of language skills, namely the ability to listen, speak, read, and write. The basic skills in learning language are the ability to listen and speak. If these basic skills are weak, students’ interest in learning Mandarin will decrease. Therefore, the author chose this topic as a research topic. The main objective of the research is to determine the level of interest of students from Bachelor of Mandarin Language Education Study Program of Indonesian Christian University towards Mandarin listening and speaking courses. Another aim is to find out the factors that influence the level of interest in learning Mandarin, such as school factors and their facilities, lecturer factors, teaching method factors, as well as lecturer and student relationship factors. This research uses the questionnaire survey method to investigate the students of Bachelor of Mandarin Language Education Study Program of Indonesian Christian University who are currently or have taken Mandarin listening and speaking courses. The result indicates that the students have quite high interest at Mandarin listening and speaking courses. Keywords: Learning Mandarin, listening and speaking courses, student’s interest, Indonesian Christian University